Ghosts in the ancient Near East: weak or powerful? - Scurlock, Jo Ann (Hebrew Union College annual / Jewish Institute of Religion, 1997)
Explicit or implicit in arguments that ancient Israelites neither sought assistance from the dead nor feared their retribution is the notion that ancient Mesopotamians (who are generally acknowledged as practicing some form of ancestor cult) did not share the Yahwist view of the pitiable dead as expressed in such passages as Ecclesiastes 9:4ff. It is indeed difficult to imagine that ancient Mesopotamians would have had any cause to regard the dead as pitiably weak and helpless, given the terrible fright and sometimes gruesome physical illnesses alleged to have been inflicted by angry ghosts. First impressions can, however, be deceptive. Although ancient Mesopotamian ghosts were capable of wreaking havoc in the world of the living they were, as a class, characterized as stupid, weak, and helpless. After death, the average ancient Mesopotamian ghost, provided that he was kept happy with a continuous series of mortuary offerings on the part of his family, "slept" away his afterlife safely imprisoned in the Netherworld. Even if, therefore, Israelite ghosts were conceived of on a popular level as essentially and characteristically silent, weak, and helpless, it by no means follows that the ancient Israelites practiced no form of ancestor cult.